2017
DOI: 10.7752/jpes.2017.02097
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of the work is to determine the characteristics of the speed of reaction in representatives of cyclic sports (swimmers) in comparison with representatives of game sports (basketball players) and to reveal the differences in the speed of simple and complex reactions in swimmers and basketball players of different qualifications. Material and methods. In this study, methods were used to determine the psychophysiological abilities of athletes in terms of time indicators of a simple and complex reaction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…This indicates a highly structured work of the body in the athlete of high qualifications. Similar data were obtained by us earlier in studies of the structure of the preparedness of basketball players [12,21,22]. it was observed that with the increase in the level of sportsmanship, athletes increased the number of correlation links between different types of preparedness; there are interrelations between those indicators that have not been interconnected previously.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This indicates a highly structured work of the body in the athlete of high qualifications. Similar data were obtained by us earlier in studies of the structure of the preparedness of basketball players [12,21,22]. it was observed that with the increase in the level of sportsmanship, athletes increased the number of correlation links between different types of preparedness; there are interrelations between those indicators that have not been interconnected previously.…”
Section: Discussionsupporting
confidence: 87%
“…of particular importance is the problem associated with the maximum manifestation of physical qualities, for example, in athletics. Currently, achievements in athletics are approaching the peak of human capabilities [19,20], and the training process in the sport of higher achievements has reached the maximum values of volume and intensity of physical exertion [21,22]. Therefore, the search for ways to improve the efficiency of the training process by optimizing it without increasing the volume and intensity of the loads, and also by taking into account and applying the training factors to enhance the sporting skills is of particular relevance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reviews and book articles deal with various aspects of a human physical activity as an exercise that collaborates with other aspects of lifestyle to influence the molecular substrates of cognition; the understanding of the mechanisms by which exercise affects cognitive abilities has been nourished from several fronts as well as excellent performance is determined by adaptive changes in the mechanisms of heart rate (HR) regulation (Platonov, 2004;Solodkov, 2005;Blagoy, 2015;Andrieieva, 2017;Kozina, 2017;Melnyk, 2017). With respect to any physical activity we should consider physical load and the impact of physical intense exercise on psycho-emotional state and perceptual-cognitive performance that is dependent on the type of the induced physical exercise (Dudnuk, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…or martial arts influence the development of psychophysiological functions. This is followed by a reduction in the reaction time for visual and auditory stimuli, increased speed of operational thinking, reduced response time of choice, increased stability of reaction time during multiple tests for determination of reaction time, reduction of errors in response to various stimuli [16][17][18].…”
Section: Introductionmentioning
confidence: 99%